TonEBP Suppresses the HO-1 Gene by Blocking Recruitment of Nrf2 to Its Promoter - Yoo, Eun Jin; Lee, Hwan Hee; Ye, Byeong Jin; Lee, Jun Ho; Lee, Chae Young; Kang, Hyun Je; Jeong, Gyu Won; Park, Hyun; Lim, Sun Woo; Lee-Kwon, Whaseon; Kwon, Hyug Moo; Choi, Soo Youn (Frontiers in Immunology, 2019)
TonEBP is a key transcriptional activator in macrophages with an M1 phenotype. High expression of TonEBP is associated with many inflammatory diseases. Heme oxygenase-1 (HO-1), a stress-inducible protein, is induced by various oxidative and inflammatory signals, and its expression is regarded as an adaptive cellular response to inflammation and oxidative injury. Here, we show that TonEBP suppresses expression of HO-1 by blocking Nrf2 binding to the HO-1 promoter, thereby inducing polarization of macrophages to the M1 phenotype. Inhibition of HO-1 expression or activity significantly reduced the inhibitory responses on M1 phenotype and stimulatory effects on M2 phenotype by TonEBP knockdown. Additional experiments showed that HO-1 plays a role in the paracrine anti-inflammatory effects of TonEBP knockdown in macrophages. Identification of HO-1 as a downstream effector of TonEBP provides new possibilities for improved therapeutic approaches to inflammatory diseases.